Monocytes, particularly nonclassical ones, lose their opsonic and nonopsonic phagocytosis capacity during pediatric cerebral malaria - Vianou, Bertin; Royo, Jade; Dechavanne, Sébastien; Bertin, Gwladys I.; Yessoufou, Akadiri; Houze, Sandrine; Faucher, Jean-François; Aubouy, Agnes (Frontiers in Immunology, 2024)
Innate immunity is crucial to reduce parasite burden and contribute to survival in severe malaria. Monocytes are key actors of the innate response and, like macrophages, are plastic cells whose function and phenotype are regulated by the signals from the microenvironment. In the context of cerebral malaria (CM), monocyte response constitutes an important issue to understand. We previously demonstrated that decreased percentages of non-classical monocytes were associated with death outcome in CM children. In the current study, we postulated that monocyte phagocytosis function is impacted by the severity of malaria infection. To study this hypothesis, we compared opsonic and non-opsonic phagocytosis capacity of circulant monocytes from Beninese children with uncomplicated malaria (UM) and CM. For the CM group, samples were obtained at inclusion (D0), and 3 and 30 days after treatment (D3, D30). Phagocytosis capacity of monocytes and their subsets were characterized by flow cytometry and transcriptional profiling by studying genes known for their functional implication in infected-red blood cells (iRBC) elimination or immune escape. Our results confirm our hypothesis and highlight the higher capacity of non-classical monocytes to phagocyte iRBC. We also confirm that a low number of non-classical monocytes is associated to CM outcome when compared to UM, suggesting a mobilization of this subpopulation to the cerebral inflammatory site. Finally, our results report suggest the implication of the inhibitory receptors LILRB1, LILRB2 and Tim3 in phagocytosis control. Taken together, these data provide a better understanding of the interplay between monocytes and malaria infection in the pathogenicity of CM.